1983
DOI: 10.1128/mcb.3.9.1656
|View full text |Cite
|
Sign up to set email alerts
|

Reduced synthesis of pp60src and expression of the transformation-related phenotype in interferon-treated Rous sarcoma virus-transformed rat cells.

Abstract: Treatment of Rous sarcoma virus-transformed rat cells with rat interferon-ot (specific activity, 106 U/mg of protein) for 24 h caused a 50% reduction in intracellular pp60Wrc-associated protein kinase activity. Staphylococcuts aurelus V8 protease digestion of pp6Osr(, derived from 32P-labeled monolayer cultures incubated with or without interferon, revealed no differences either in the phosphopeptide pattern or in the phosphoserine-phosphotyrosine ratio. However, [3H]leucine pulse-labeling experiments showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
3

Year Published

1986
1986
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 47 publications
2
10
3
Order By: Relevance
“…Therefore, the reduction in 32p radioactivity in the p60sr, fraction could have resulted from inhibition (probably inactivation, see below) of the protein kinase activity of p6Osrc but not from a reduction in the amount of p6Osrc by these antibiotics in the cells. This is in contrast to the recent report that interferon selectively inhibits synthesis of p6Osrc in RSV-transformed rat cells, resulting in reversion to the normal phenotype (23).…”
Section: Discussioncontrasting
confidence: 54%
“…Therefore, the reduction in 32p radioactivity in the p60sr, fraction could have resulted from inhibition (probably inactivation, see below) of the protein kinase activity of p6Osrc but not from a reduction in the amount of p6Osrc by these antibiotics in the cells. This is in contrast to the recent report that interferon selectively inhibits synthesis of p6Osrc in RSV-transformed rat cells, resulting in reversion to the normal phenotype (23).…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, no such reversion was observed in repeated studies with IFN-treated RS504, an NIH 3T3 cell line transformed by the mutated EJras (33). Revertants of RS485 that were propagated in the continuous presence of 200 IU of IFN-cx/p per ml were nontumorigenic (34) and produced four-to eightfold less ras mRNA and ras-encoded p21 than parental RS485 (32).Our present studies showed that in contrast to the reversibility of cellular changes seen with short-term (several days) exposure to IFN (14,20,25,30), the phenotypic reversion of RS485 established after 1 to 2 months of IFN treatment persisted long after treatment was discontinued. The persistent revertants (PRs) expressed high levels of p21, yet were not tumorigenic.…”
contrasting
confidence: 52%
“…Our present studies showed that in contrast to the reversibility of cellular changes seen with short-term (several days) exposure to IFN (14,20,25,30), the phenotypic reversion of RS485 established after 1 to 2 months of IFN treatment persisted long after treatment was discontinued. The persistent revertants (PRs) expressed high levels of p21, yet were not tumorigenic.…”
contrasting
confidence: 41%
“…In our cases, the p21 expression was greater in advanced (stage III) MM and closely related with BMPC infiltration. Alpha-interferon reverses a number of transformed, tumorigenic cell lines (Brouty-Boye et al, 1985) and some reversions are associated with a significant reduction in the expression of the oncogenes implicated in the transformation process (Lin et al, 1983;Samid et al, 1984). If we speculate that the effectiveness of this agent in MM is due to a similar mechanism, its activity may be evaluated with the FCM method we employed to detect p21 expression.…”
Section: Resultsmentioning
confidence: 99%